STRATEGI GURU PENDIDIKAN AGAMA ISLAMDALAM PEMBINAAN AKHLAK SISWA DI SMA NEGERI 25 BONE - Mulyana, Mulyana; Ridwan, Ridwan (Institut Agama Islam Negeri (IAIN) Bone, 2021)
This paper examines the strategy and impact of the implementation of PAI teacher strategies in fostering the morals of students at SMA Negeri 25 Bone. The type of research used in this study is a qualitative research with descriptive analysis. The research used instruments in the form of interview guides, observation guidelines and documentation tools. This research was conducted at SMA Negeri 25 Bone located on Jl. Axis Bone- Makassar KM. 43 Bengo-Lappajupeng Kec. Bengo Kab. Bone. The results of the study show that the strategy implementation of PAI teachers in developing the morals of SMA Negeri 25 Bone students is oriented towards intra-curricular, co-curricular and extra-curricular activities including giving advice and habituation to mutual respect and appreciation, the habit of reading the Qur'an before learning begins, and the habit of maintaining the cleanliness and beauty of the school. Meanwhile, the results of the implementation of the PAI teacher strategy at SMA Negeri 25 Bone in fostering student morals, showed an increase in students' noble character such as increasing discipline, politeness and honest attitude of students.The research implication is that PAI teachers can foster and improve students' noble character through harmonious cooperation between schools, parents, communities, and the government for the sustainability of education. This is very reasonable, because of the lower morality and character of students, and the disconnection of all components in an effort to help implement a dynamic education for future generations.